2011
DOI: 10.1146/annurev-psych-120709-145357
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Mind, and the Brain: Current Evidence and Future Directions

Abstract: Current research on culture focuses on independence and interdependence and documents numerous East-West psychological differences, with an increasing emphasis placed on cognitive mediating mechanisms. Lost in this literature is a time-honored idea of culture as a collective process composed of cross-generationally transmitted values and associated behavioral patterns (i.e., practices). A new model of neuro-culture interaction proposed here addresses this conceptual gap by hypothesizing that the brain serves a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
415
1
10

Year Published

2016
2016
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 598 publications
(435 citation statements)
references
References 127 publications
9
415
1
10
Order By: Relevance
“…Notably, the logic of this model seems closer than that of previous measurement models to Markus and Kitayama's original theorizing (see Markus & Kitayama, 1991, Table 1) as well as subsequent revisions of their perspective (Kitayama & Uskul, 2011;Markus & Kitayama, 2010). If independence and interdependence are priorities of cultural systems, rather than properties of individuals, then there is no reason to expect that they should form monolithic dimensions of individual differences (Kitayama et al, 2009), and this is what we found.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Notably, the logic of this model seems closer than that of previous measurement models to Markus and Kitayama's original theorizing (see Markus & Kitayama, 1991, Table 1) as well as subsequent revisions of their perspective (Kitayama & Uskul, 2011;Markus & Kitayama, 2010). If independence and interdependence are priorities of cultural systems, rather than properties of individuals, then there is no reason to expect that they should form monolithic dimensions of individual differences (Kitayama et al, 2009), and this is what we found.…”
Section: Discussionsupporting
confidence: 69%
“…Developmental psychologists sought to identify the prevailing theories, styles, and practices of parenting that foster development of independent or interdependent selves in different cultures (reviewed by Greenfield, Keller, Fuligni, & Maynard, 2003;Kağıtçıbaşı, 2007;Keller, 2007). Neuroscientists have begun to identify differences in brain activity that correlate with measures of independence and interdependence (reviewed by Kitayama & Uskul, 2011). However, the success of this perspective has arguably contributed to the prevalence of a rather black-and-white view of cultural diversity, which we believe was not the authors' original intention (see Markus & Kitayama, 2003.…”
Section: Copyright and Reusementioning
confidence: 99%
See 3 more Smart Citations